ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI KINERJA GURU (STUDI KASUS GURU SMP SWASTA KOTA JUANG KABUPATEN BIREUEN) - Mawardi, Mawardi; Iskandar, Raihan; Muttaqim, Hakim (IndOmera, 2023)
The research was conducted using a quantitative descriptive method in assessing the internal factors that affect teacher performance. The factors studied were limited to 3 (three) things, namely the level of education, teacher competence and teaching experience. Study of teachers working in private junior high schools in Juang City, Bireuen Regency. Alleged research, there is a direct influence from the causality of the three observed exogenous variables on the endogenous variable "teacher performance". There is also a correlation between exogenous variables both in substance and empirically. So the analysis uses a path model approach by building a structural framework in the form of a path diagram. The results of the study show that there are direct and indirect effects: 1) the factor of teacher education on teacher performance is 34.71%. 2) the teacher competency factor on teacher performance is 37.58%. 3) the factor of teaching experience on teacher performance is 41.8%. 4) Simultaneously the level of education, competency and teaching experience have a significant effect on the performance of private junior high school teachers in Kota Juang District, Bireuen Regency based on a coefficient of determination of 49.1%. While the remaining role of the teacher's internal variables that were not examined was 50.9%.